'I like it': Exploring teachers' motivation for using classroom-based physical activity in Danish public schools from a self-determination perspective. Results from a mixed methods study. (October 2021) - Knudsen, Louise Stjerne; Skovgaard, Thomas; Bredahl, Thomas Viskum Gjelstrup
Abstract: In the context of a national physical activity policy, this study explores Danish school teachers' motivation for using classroom-based physical activity. Through a mixed methods approach, the study reveals a number of key motivational drivers such as supporting teachers' autonomy, competence and collaboration. Reversely, the study also reveals barriers for integrating physical activity, such as a lack of time, lack of support and lack of appropriate training. Teachers are important facilitators in the integration of daily physical activity. However, work still needs to be done in order to support teachers to integrate physical activity into teaching routines effectively and successfully. Highlights: Teachers are key facilitators in the integration of school-based physical activity. Teachers are supportive of and interested in classroom-based physical activity. Teachers' motivation and commitment is central to classroom activities. Classroom-based physical activity may require new and creative teaching approaches. Schools should encourage and support collaboration among teachers.